ECG Quiz 38 - Answer - Millar, Rob Scott; Chin, Ashley (SA Heart Journal, 2017)
There is a regular bradycardia, around 54bpm. The most striking feature is deep T-wave inversion in leads V1 to V4. There are many possible causes for this pattern.